THE IMPORTANCE OF COOLING REGIME IN THE FORMATION OF MELT INCLUSIONS IN OLIVINE CRYSTALS IN HAPLOBASALTIC MELTS - Goldstein S.B.; Luth R.W. (My University, 2006)
Experiments using synthetic mafic liquids of composition Fo30Di30An40 and Fo22Di58An20 (wt.%) were conducted to constrain the range of cooling regimes over which melt inclusions form in olivine crystals. In one set of experiments, batches of melt were cooled at rates of 1,7, 10, 50, 100, and 250°(2/h from supefliquidus temperatures to 1350 or 1300°C, below the liquidus temperature (1450°C) of both bulk compositions. In a second set of experiments, samples were cooled at rates of 100°C/h and 250°C/h to temperatures of 1300, 1350, or 1400°C, where they were held isothermally for six hours before quenching, Melt inclusions form at cooling rates between 7°C/h and 250°C/h in experiments with no isothermal period. More abundant inclusions formed in the second set of experiments, with an isothermal period. In some cases, melt inclusions form by the simultaneous growth or oriented agglomeration of neighboring platy crystals. This mechanism is consistent with observations of linear trends of inclusions and re-entrants, as well as the composite appearance of platy crystals and long narrow re-entrants between plates.